First clinical trial of a novel caspase inhibitor: anti-apoptotic caspase inhibitor, IDN-6556, improves liver enzymes - Valentino, K L; Gutierrez, M; Sanchez, R; Winship, M J; Shapiro, D A (International journal of clinical pharmacology and therapeutics, 2003)
To evaluate the safety of IDN-6556, a novel anti-apoptotic pan-caspase inhibitor, administered in single and multiple ascending doses in normal volunteers and patients with hepatic dysfunction. IDN-6556 was administered as a 30-minute intravenous infusion in rising doses to 3 groups: Group A, normal volunteers, given as a single infusion, Group B, normal volunteers, given q.i.d. for 7 days, Group C, patients with hepatic impairment (elevated transaminases, alanine transaminase, ALT and aspartate transaminase, AST), given q.i.d. for 7 days. The drug was well tolerated up to 10 mg/kg/infusion for a single dose, and 1.5 mg/kg/infusion q.i.d. for 7 days, with the dose-limiting adverse event of phlebitis or inflammation at the site of the infusion. This toxicity was predicted from animal studies. Clinically and statistically meaningful dose-related falls in transaminases were seen in all but 1 of the hepatic impaired patients. Two-way ANOVA analyses of the changes for all the IDN-6556 groups combined versus placebo were: ALT absolute change: p < 0.0001 and % change: p = 0.012, AST absolute and % changes: p < 0.0001. After discontinuation of the drug (after 7 days of dosing), the transaminases rapidly returned to the pre-treatment levels. Following intravenous administration of a novel anti-apoptotic caspase inhibitor, adverse events were mild-to-moderate in severity, resolved in a few days and did not result in any subject terminating treatment prematurely. The effects in hepatic impaired patients appear to be consistent with both the administration and subsequent abrupt withdrawal of an effective hepatoprotective drug that delays cell death in hepatocytes.